Spatial patterns of phylogenetic and species diversity of Fennoscandian vascular plants in protected areas - Damaris M. Matten; Ida M. Mienna; Vanessa C. Bieker; Brent D. Mishler; Victoria S. Moen; Malene Nygaard; Katariina E. M. Vuorinen; Mika Bendiksby; Michael D. Martin; James D.M. Speed (Biodiversity and Conservation, 2023)
Protected areas are one of the main strategic means for conserving biodiversity. Yet, the design of protected areas usually neglects phylogenetic diversity, an important diversity measure. In this paper we assess the phylogenetic diversity and species richness of vascular plants in Fennoscandian protected areas. We evaluate how much species richness and phylogenetic diversity is found within and outside protected areas, and the differences in plant diversity between different categories of protected areas. We also assess the differences in the diversity-area relationship of the different protected area categories in terms of both species richness and phylogenetic diversity. We build a multi-locus phylogeny of 1,519 native vascular plants of Norway, Sweden, and Finland. We estimate the phylogenetic diversity and species richness by combining the phylogeny with publicly available occurrence data and the currently protected area system of Fennoscandia. Our results indicate that protected areas in Fennoscandia hold more plant diversity when larger, and that phylogenetic diversity increases faster with area than species richness. We found evidence for more plant diversity outside of protected areas of the different countries of Fennoscandia than inside of protected areas, but no evidence for plant diversity differences between areas with different protection status. Hence, our results indicate that the current protected area system in Fennoscandia is no more effective in conserving phylogenetic diversity and species richness of vascular plants than a random selection of localities. Our results also indicate that planning conservation strategies around phylogenetic diversity, rather than species richness, might be a first step to protect vascular plant diversity more effectively.